Editorial - International Journal of Sustainable Energy Planning and Management Vol 5 - Poul Alberg Østergaard (International Journal of Sustainable Energy Planning and Management, 2015)
This editorial introduces the fifth volume of the International Journal of Sustainable Energy Planning and Management. Topics include electricity for heating purposes based on a case study of Tirana, the Norwegian system for licensing wind power plants, analyses of energy security for the Indian residential sector and finally the link between energy sector reforms, sustainable development and energy use.